Performance Analysis of FII on Indian Stock Exchange - K. , Chitradevi; G. , Kalpana (International Journal of Psychosocial Rehabilitation, 2020)
Foreign institutional investment is the most important crucial role. This research study will benefit the foreign institutional investors. The research paper has analyzed the impact of foreign institutional investment and the national stock exchange in India and the influence between the foreign institutional investment and the NSE, the FIIs flow into Indian stock markets. The study was taken 18 years into consideration, from 2000-01 to 2017-18. The period has been selected so that the flow of FII and the stock market can be ascertained from the initial period FII investment was permitted in India. NSE is one of the biggest indices, so it was selected for the study. The present study has been set out to accomplish the following objectives. To analyze the relationship between foreign institutional investment and capital market segments on the National Stock Exchange in India. To determine the foreign institutional investment and capital market segments on the National Stock Exchange in India. The present study covers a period of 18 years, taking from 2000-01 to 2017-18. There is no significant relationship between the capital market segment on the national stock market and foreign institutional investment. Foreign institutional investment is good fluctuation in the time period from 2000-01 to 2017-18. There has been a correlation between foreign institutional investment in equity and capital market segments of the National Stock Exchange in India. The relationship between the variables was significant at the 1% level. There was a result that proved a moderate impact between the foreign institutional investment and capital market segments of the national stock exchange. Therefore, the null hypothesis is rejected, and the alternative hypothesis is accepted. The foreign institutional investment is the positive impact on NSE.